Nobody else but you [videorecording (DVD)] - Hustache-Mathieu, Gérald, 1968-; Hustache-Mathieu, Gérald, 1968-; Rouve, Jean-Paul, 1967-; Quinton, Sophie, 1976- (First Run Features, 2011)
Rousseau is a bestselling crime novelist from Paris, troubled by writer's block. Candice Lecoeur is a local beauty gracing the famous Belle de Jura cheese packaging who has gotten it into her head that she might well be the reincarnation of Marilyn Monroe. The two will meet in the coldest village in France, but only after Candice has been found dead.